Intentions’ determinants of Malaysian muslim travellers to patronize restaurants in South Korea - Jaihan, Norfazila; Hashim, Khairusy Syakirin Has-Yun; Ahmad, Anis Najiha (IIUM Press, 2022)
Observations of Muslim travellers have shown their interest in travelling in Muslim minority countries, particularly South Korea. However, the number of Halal Certified Restaurant (HCR) is inadequate, restricting their gastronomic experience. Another alternative is restaurants that do not have Halal certification but also provide Halal food, known as Muslim Friendly Restaurant (MFR). Thus, the intention of Malaysian Muslim travellers to patronise the restaurants was investigated by applying the extended Theory of Planned Behavior (TPB). Through the distribution of questionnaires, 310 data were successfully collected. However, after the data screening process, only 292 data were found to be valid for further analysis using SPSS26 and SmartPLS 3.2.8. The three factors in TPB, namely attitude, subjective norm, and perceived behavioural control, were significant and positively related to the intention to patronise HCR and MFR. However, religiosity and restaurant attributes did not significantly impact the intentions.